Dietary fresh fish and processed fish intake and the risk of glioma: A meta-analysis of observational studies - Zhang, Zihe; Xin, Jiangze (Cellular and Molecular Biology, 2019)
The current study was to evaluate the predicted role of dietary fresh fish and processed fish intake for risk of glioma. Databases of Web of Science, PubMed, and Wan Fang Med Online were retrieved up to Jan 31th, 2018. Eligible studies were identified based on defined inclusion criteria. Summarized results of relative risk (RR) with corresponding 95% confidence intervals (CI) were calculated using a random effects model. Sensitivity analysis and publication bias were also performed. The final analysis in this report included a total of 9 articles. The summarized RR and 95%CI from 8 studies for dietary fresh fish intake and glioma risk was 0.823 (95%CI= 0.698-0.970), with no evidence of significant between-study heterogeneity (I2=43.6%, P=0.088). Moreover, positive associations were also found both in Caucasian populations and Asia populations. Seven studies were used to assess the relationship between dietary processed fish intake and the risk of glioma. Significantly increased risk of glioma was found for the highest category of dietary processed fish intake [summarized RR= 1.554, 95%CI= 1.169-2.066, I2= 72.1%, P= 0.001], especially among Caucasian populations. No publication bias was found. In summary, findings from this meta-analysis concluded that dietary fresh fish intake could reduce the risk of glioma. However, very high processed fish intake had a significant association with increased glioma risk.